2012
DOI: 10.1200/jco.2011.38.0303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Mellitus and Insulin Use on Survival After Colorectal Cancer Diagnosis: The Cancer Prevention Study-II Nutrition Cohort

Abstract: Patients with CRC and T2DM have a higher risk of mortality than patients with CRC who do not have T2DM, especially a higher risk of death from CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 31 publications
6
91
0
2
Order By: Relevance
“…It is possible that DM has different prognostic association on colon and rectal cancer. In a large prospective cohort, however, Dehal et al [24] showed that DM was nonsignificantly associated with higher cancer-specific mortality (relative risk, 1.29; 95% CI, 0.98 to 1.70) in patients with nonmetastatic "colorectal" cancer. Furthermore, a singleinstitute study showed that DM was significantly associated with shorter CSS in patients with resected stage I to stage III colon cancer when no adjustments for adjuvant chemotherapy and comorbidities were made in the multivariate analysis [12].…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that DM has different prognostic association on colon and rectal cancer. In a large prospective cohort, however, Dehal et al [24] showed that DM was nonsignificantly associated with higher cancer-specific mortality (relative risk, 1.29; 95% CI, 0.98 to 1.70) in patients with nonmetastatic "colorectal" cancer. Furthermore, a singleinstitute study showed that DM was significantly associated with shorter CSS in patients with resected stage I to stage III colon cancer when no adjustments for adjuvant chemotherapy and comorbidities were made in the multivariate analysis [12].…”
Section: Discussionmentioning
confidence: 96%
“…Pre-existing diabetes at cancer diagnosis is also associated with poorer overall survival in patients with colorectal cancer (CRC) [5][6][7][8][9][10][11][12][13]. However, investigation of cause-specific mortality in this context has been limited, and findings have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…However, investigation of cause-specific mortality in this context has been limited, and findings have been mixed. Three studies report a relationship between diabetes and increased CRC mortality [11][12][13], although, in one of these [13], increased CRC mortality was observed in people with diabetes who were diagnosed with rectal cancer but not in those with colon cancer. Two further investigations found no significant effect of diabetes on CRC-specific mortality [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes has been linked with an increased risk of several cancers, including CRC [4][5][6]. Furthermore, diabetes has been associated with increased mortality and poorer clinical outcomes among persons with CRC [7,8]. It is therefore important that persons with diabetes receive CRC screenings according to age-appropriate guidelines [4].…”
Section: Introductionmentioning
confidence: 99%